PENGARUH RETURN BAGI HASIL(MUDHARABAH MUTLAQAH) TERHADAP PERTUMBUHAN DANA PIHAK KETIGA PADA BANK SYARIAH MANDIRI - Yun Fitriano; Okta Septiarani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The purposes of this research is to determine the effect of return for (mudharabah muthlaqah) an the growth of third party funds in Bank Syariah Mandiri. The data used are secondary data in the form of Bank Syariah Mandiri financing report from January 2017 until December 2017 which is taken through the official website of Bank Syariah Mandiri. Data analysis techniques using simple linier regression analysis method with computer program SPSS Version 21.0. this research concludes that the effect of return (mudharabah muthlaqah) is a variable that has a bis influence on the growth of third party funds in Bank Syariah Mandiri. Return on profit sharing (mudharabah muthlaqah) affects third party fund growth of 63,9 %.